Unacceptable circumstances in takeovers - Ambaras Khan, Mushera Bibi (LexisNexis, 2010)
The board of the target should not apply defences that protect management at the expense of shareholders. Due to this reason, takeovers law does not only regulate takeover activities but it also focuses on the aspect of governance to ensure that the board of the target does not abuse its power. This will in turn ensure that the interest of shareholders, especially the minority, in circumstances where the control of a company is likely to change, is protected. This will indirectly protect the integrity of the securities markets with a view to maintaining investor confidence in the capital market. Section 217(5) of the Capital Market Services Act 2007 lays down the foundation of the Malaysian takeovers law. As a general rule, directors are tied up with the fiduciary duties they owe to a company. In addition to the fiduciary duties provided for in the Companies Act 1965, the Malaysian Code on Take-Overs and Mergers 1998 (‘the Code’) prevents the board of the target company from taking action which would have the effect of frustrating a takeover bid. It prohibits the board of the target from taking suchactions, whether during the course of an offer or even before the date of the offer if they have reason to believe that a bona fide offer might be imminent, unless they have obtained their shareholders’ approval.